Pelatihan Kerajinan Batik Dalam Rangka Mewujudkan Kampung Batik sebagai Ikon Khas Kelurahan Pakal - Tegar Zakaria Nugraha; Gideon Setyo Budiwitjaksono; Ilvia Azhari Salsabila; Arie Dwi Riskiyanti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The majority of housewives in the Pakal sub-district work as housewives whose skills are not honed. In addition to the lack of assistance and training they have received, their capacity and abilities related to creativity management are also limited. This indirectly affects household economic income which is less than optimal. Through one of the work programs of the East Java KKNT-MBKM UPN "Veteran" Group with an entrepreneurial and creative economy scheme, namely Batik Craft Training in Pakal Village, Group 40 hopes that this service program can provide understanding and educate the community around especially to housewives about the techniques and processes of making batik which can later be useful as creativity that produces. The model developed is a service based on empowerment and mentoring. The series of training implementation includes basic ideas, observation, idea fixation, and execution which includes socialization related to the delivery of the batik craft training program to be carried out to residents around the Pakal village, to the process of mentoring batik craft training accompanied by the Family Welfare Empowerment (PKK) Kelurahan Pakal, in order to realize Batik UMKM to support the realization of a batik village in Pakal Village. Therefore, the Pakal Village community is expected to be able to take an active and creative role in improving the community's economy.